Transformation of local bubble rise velocity measurements to global results: Shown by a Monte Carlo simulation of a fluidized bed. (April 2015) - Maurer, Simon; Rüdisüli, Martin; Teske, Sinan L.; Schildhauer, Tilman J.; van Ommen, J. Ruud; Biollaz, Serge M.A.; Wokaun, Alexander
Highlights: Discussion of the bias in local bubble rise velocity measurements. Successful transformation of local to global bubble rise velocity. Monte Carlo model for simulation of bubbles in a fluidized bed. Abstract: To design bubbling fluidized bed reactors and study chemical reactions, the knowledge of hydrodynamic properties, such as bubble size, rise velocity and hold-up is of importance. Local measurements of those properties are valuable, but do not automatically reflect the properties of the full bed. In the manuscript a method based on Bayes' theorem is developed, which helps to transform local bubble rise velocity measurements into a global result. The transformation method was tested by means of a Monte Carlo simulation.